(untitled) (Research, Society and Development, 2021)
Chronic Kidney Disease is characterized as a Chronic Non-Communicable Disease that reaches worldwide proportions. Factors that contribute to the advancement of this situation are the increased incidence of basic diseases such as Systemic Arterial Hypertension (SAH) and Diabetes mellitus (DM) in the world population and the high occurrence of Acute Kidney Injury in in-hospital settings. Objective: To identify the situation of patients with injury renal who underwent hemodialysis in a private hospital in the interior of São Paulo. Methods: a cross-sectional, retrospective, descriptive study, with a quantitative approach, carried out through the analysis of electronic medical records of a private hospital, between January to June 2017. An exploratory statistical analysis was carried out, with a frequency analysis of the data obtained. Results: 58 medical records were analyzed. The average age identified was 70,7 years (± 15,5), with a minimum of 28 years and a maximum of 98 years. As for health conditions, 63,7% had a history of Systemic Arterial Hypertension, while half of the sample had heart disease and Diabetes mellitus was found in 41,3% of the sample. The initial diagnosis related to cardiovascular diseases corresponded to 32,7% of the data, sepsis to 20,6%, and renal insufficiencies were present in 8,6% of these diagnoses. Regarding Renal Replacement Therapy, approximately 80% had Acute Kidney Disease, with temporary triple-lumen vascular access predominating. Conclusion: identifying the factors that contribute to the picture of in-hospital CKD provides a better condition to safeguard patients’ lives, as well as enabling the early identification of risk factors for worsening renal function.